O Projeto Integrado de Arquitetura. Algumas Considerações Metodológicas - Naveiro, Ricardo M. (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 1993)
This paper is based in my D.Sc. research done at FAU/USP where was surveyed the technological innovations observed in the manufacturing industry and analised the contribution of CAD to improve the integration between design and manufacturing areas. The same subject is developped here for the construction industry, highlighting some applications of CAD in the archictectural project and its contribution to achieve an integrated design environment. The paper begins with the discussion on technology innovation in both, manufacturing industry and construction industry. The main differences are pointed and some concepts are addapted to architectural design. We finish the paper presenting some CAD applications in archictectural design specially its use as a tool for design retrieval and identifying some integration chains that can be implemented with the use of this technology